Meta-Analyses of Reading Intervention Studies Including Students With Learning Disabilities: A Methodological Review. (May 2023) - King, Seth; Wang, Lanqi; Datchuk, Shawn M.; Rodgers, Derek B.
Learning disabilities (LD) may affect a range of academic skills but are most often observed in reading. Researchers and policymakers increasingly recommend addressing reading difficulties encountered by students with LD using evidence-based practices, or interventions validated through multiple, high-quality research studies. A valuable tool in identifying evidence-based practices is the meta-analysis, which entails statistically aggregating the results obtained through primary studies. Specific methods used in meta-analyses have the potential to influence their findings, with ramifications for research and practice. This review assessed the methodological features of the systematic reviews and analytic procedures featured in meta-analyses of reading intervention studies that included students with LD written between 2000 and 2020. Identified articles ( N = 23) suggest that meta-analyses have become more prevalent and transparent over time, notwithstanding issues related to publication bias and the opacity of coding procedures. A discussion of implications follows a description of results.